Computer Aided Verification: 37th International Conference, CAV 2025, Zagreb, Croatia, July 23-25, 2025, Proceedings, Part II (Lecture Notes in Computer Science, 2025)
This open access 4-volume set constitutes the proceedings of the 37th International Conference on Computer Aided Verification, CAV 2025, held in Zagreb, Croatia, in July 23-25, 2025. The 51 regular papers presented together 24 tool papers, 4 casestudy papers in these proceedings were carefully reviewed and selected from 305 submissions. The accepted papers cover a wide spectrum of topics, from theoretical results to applications of formal methods. These papers apply or extend formal methods to a wide range of domains such as concurrency, machine learning and neural networks, quantum systems, as well as hybrid and stochastic systems.